Christian spirituality in the Dolores Aleixandre theology - Soto Rivas, Víctor Pablo (2013)
The article presents the most striking features of the Christian spirituality of Dolores Aleixandre who has managed to show the way of being a Christian from a reading of the Word that emphasizes a) circular and fraternal dream of Jesus who sees his church as a community he presides and in which all other men and women are brothers and his disciples, b) sense of humor and c) applying the teachings to the full and integral life of the person. The article also notes that this rereading is all thanks to the new female perspective she imbues biblical exegesis.